The real story behind the 13 colonies - Honders, Christine (Real story: debunking history., 2020)
Examines common stories from the Colonial period and debunks common myths from Thanksgiving to the Salem Witch Trials and Pocahontas. Includes illustrations, sidebars, a glossary, and an index.